INTEGRATION OF PROJECT MANAGEMENT AND DIGITAL MARKETING TO IMPROVE FINANCIAL PERFORMANCE: A QUALITATIVE STUDY OF IT COMPANIES IN SURAKARTA - Prasetyaningrum, Nurita Elfani; Sudalyo, Ramadhian Agus Triono; Trisnowati, Juni; Sarsiti, Sarsiti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Abstract : Information technology (IT) companies in Surakarta are increasingly under pressure to improve their financial performance amid growing market competition. Project management has been recognized as an effective tool for managing IT projects; however, its implementation and its impact on the financial performance of companies are not fully understood. This research aims to explore how the implementation of project management affects the financial performance of IT companies in Surakarta through a qualitative approach. The research method involves in-depth interviews with project managers, project team members, and relevant stakeholders in 35 IT companies across seven districts and cities in Surakarta. Data analysis is conducted using a qualitative approach focusing on themes emerging from the interviews. The results of this research have shown that the implementation of project management has a significant impact on improving the financial performance of information technology companies in Surakarta. The study successfully identified several key findings: 1) Increased Operational Efficiency; 2) Cost Reduction; 3) Improved Product and Service Quality; and 4) Efficient Resource Allocation. Thus, this research provides an important contribution to the development of theory and project management activities, as well as IT company activities in Surakarta. These findings can be used as a basis for the development of better strategies and policies in project management, as well as strengthening the position of IT companies in competitive markets.